Yeast and fungal prions: a help or a hindrance? - Wickner, Reed (Henry Stewart Talks, 2008)
[URE3] and [PSI+] not found in wild strains indicating they are harmful, [Het-s] may benefit its host or may result from "meiotic drive", Some "prion domains" cannot be prions, "Prion domains" have non-prion functions, Rapid evolution of prion domains may protect against infection
Archived at 2021/02/25